2012
DOI: 10.1364/josab.29.000714
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Doppler shift of a phase-conjugated photon

Abstract: The rotational Doppler shift of a photon with orbital angular momentum ±ℓ is shown to be an even multiple of the angular frequency Ω of the reference frame rotation when photon is reflected from the phase-conjugating mirror. The one-arm phase-conjugating interferometer is considered. It contains N Dove prisms or other angular momentum altering elements rotating in opposite directions. When such interferometer is placed in the rotating vehicle the δω = 4(N + 1/2)ℓ · Ω rotational Doppler shift appears and rotati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Frame rotation has also been employed when considering reflection and interference patterns [7][8][9]. However, the effect of frame rotation on the OAM of light itself has yet to be fully explored.…”
mentioning
confidence: 99%
“…Frame rotation has also been employed when considering reflection and interference patterns [7][8][9]. However, the effect of frame rotation on the OAM of light itself has yet to be fully explored.…”
mentioning
confidence: 99%
“…From equation (19), it can be concluded that change in frequency of one photon (or a gi for n photons) is directly proportional to the AM transferred by the relative rotational movement of the traversed object (Ω) with respect to the circularly polarized light beam traversing it (σ = ±1) [19,20]. Therefore, the interaction of light rays with the material implies that large energy exchanges in the form of AM would produce a strong rotational Doppler effect [19,21].…”
Section: Resultsmentioning
confidence: 99%
“…The synchronized modes of empty resonator form an almost perfect periodic lattice of dark spots [9]. Each dark spot is surrounded by a nearly circular flow resembling isolated optical vortex alike Laguerre-Gaussian beam [21,22]. The phase of optical field is a precise indicator of electromagnetic energy circulation [23].…”
Section: Singular Lattices and Their Vibrationsmentioning
confidence: 99%
“…A part of numerically obtained patterns is composed from zeros of amplitudes equispaced in a checkerboard geometry with alternating circulations as is shown in [8]. The macroscopic photons wavefunction Ψ ∼ E n ( r) [21] which is visualized by electric field amplitude E n ( r), demonstrates the regular lattices of field zeros with counter-rotating whirls around [ fig.6]. In contrast to optical speckle patterns [24] where vortex-antivortex pairs are distributed chaotically in space the lattice of whirls in wide-aperture lasers is periodic in space [ fig.5].…”
Section: Singular Lattices and Their Vibrationsmentioning
confidence: 99%